2018
DOI: 10.21037/atm.2018.04.36
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure targets for hypertension in patients with type 2 diabetes

Abstract: We concluded that in adults with diabetes mellitus and arterial hypertension, in order to reduce the risk of stroke, clinicians should target blood pressure at 120-130/80 mmHg, with close monitoring for all drug-related harms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 205 publications
0
14
0
Order By: Relevance
“…The current clinical parameter for diagnosing hypertension is systolic blood pressure values of 130 mmHg or more and/or diastolic blood pressure above 80 mmHg [ 181 ]. In order to reduce the risk of stroke, it has been recommended that the blood pressure of DM patients be maintained between 120 and 130/80 mmHg [ 182 ].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…The current clinical parameter for diagnosing hypertension is systolic blood pressure values of 130 mmHg or more and/or diastolic blood pressure above 80 mmHg [ 181 ]. In order to reduce the risk of stroke, it has been recommended that the blood pressure of DM patients be maintained between 120 and 130/80 mmHg [ 182 ].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…interviewer administered questionnaire was used to collect data. Questionnaire was adapted from previous published articles [3, 7, 10, 11, 13, 22, 33–35], prepared in English and translated to Amharic and retranslated to English by another person (see Additional file 1). Four data collectors and two supervisors participated in data collection.…”
Section: Main Textmentioning
confidence: 99%
“…Decreasing of SBP by 10 mmHg lead to 12% reductions of diabetes complications [9, 10]. SBP increases after 50–60 years due to age-related changes in vasculature [11].…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of randomized controlled trials (RCTs) has shown a linear relationship between the reduction in HbA 1c and major cardiovascular events . Another meta‐analysis of RCTs, showed that reaching blood pressure targets was associated with decreased risk of diabetes‐related mortality . Additionally, very low LDL cholesterol level was associated with reduced cardiovascular risk in people with type 2 diabetes .…”
Section: Introductionmentioning
confidence: 99%